Comparison of Novel Bioactive Materials in Indirect Pulp Therapy in Deciduous Teeth: An in Vivo Study - Sonu Acharya; Deepa Gurunathan (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To assess the clinical success of Biodentine, NeoPutty, and calcium hydroxide as pulp capping materials for indirect pulp capping in carious primary teeth. Material and Methods: Indirect pulp treatment was performed on 36 deciduous molars in patients with deep carious lesions. The teeth were randomly assigned to three groups (n=12): Biodentine, NeoPutty, and calcium hydroxide. Statistical analysis was conducted using SPSS software version 21.0. Pearson's Chi-square test was employed to compare success and failure rates of the materials at three different time intervals (30, 90, and 180 days) and overall success and failure rates regardless of the time intervals. Results: Different pulp capping materials yielded varying success rates. The NeoPutty demonstrated a success rate of 91.67%, the Biodentine 83.33%, and the calcium hydroxide 58.33% after 6 months. However, these differences were not statistically significant (p>0.05). Conclusion: Indirect pulp treatment with calcium silicate-based materials, such as Biodentine and NeoPutty, showed superior results compared to calcium hydroxide. Although differences in success rates were observed among the materials, they did not reach statistical significance.